Immunomodulatory effect of human bone marrow‐derived mesenchymal stromal/stem cells on peripheral blood T cells from rheumatoid arthritis patients. (11th November 2019) - Pedrosa, Mónia; Gomes, Joana; Laranjeira, Paula; Duarte, Cátia; Pedreiro, Susana; Antunes, Brígida; Ribeiro, Tânia; Santos, Francisco; Martinho, António; Fardilha, Margarida; Domingues, M. Rosário; Abecasis, Manuel; et al.
Abstract: Rheumatoid arthritis (RA) is a Th1/Th17‐mediated autoimmune disease whose current treatment, consisting in the blockage of inflammatory cytokines by disease‐modifying antirheumatic drugs, is not effective for all patients. The therapeutic potential of mesenchymal stromal/stem cells' (MSCs) immunomodulatory properties is being explored in RA. Here, we investigate the effect of human bone marrow (BM)‐MSCs on the expression of cytokines involved in RA physiopathology by the distinct functional compartments of CD4 + and CD8 + T cells from RA patients. Peripheral blood mononuclear cells from healthy individuals ( n = 6) and RA patients ( n = 12) were stimulated with phorbol myristate acetate plus ionomycin and cultured in the presence/absence of BM‐MSCs. The expression of (interleukin) IL‐2, tumor necrosis factor alpha (TNF‐α), and interferon‐gamma (IFN‐γ) was evaluated in naive, central memory, effector memory, and effector CD4 + and CD8 + T cells, whereas IL‐6, IL‐9, and IL‐17 expression was measured in total CD4 + and CD8 + T cells. mRNA expression of IL‐4, IL‐10, transforming growth factor beta (TGF‐β), cytotoxic T‐lymphocyte‐associated antigen 4, and/or forkhead box P3 was quantified in fluorescence‐activated cell sorting‐purified CD4 + T cells, CD8 + T cells, and CD4 + Treg. BM‐MSCs inhibited the production of TNF‐α, IL‐17, IL‐6, IL‐2, IFN‐γ, and IL‐9 by T cells from RA patients, mainly by reducing the percentage of cells producing cytokines. This inhibitory effect was transversal to all T cell subsets analyzed. At mRNA level, BM‐MSCs increased expression of IL‐10 and TGF‐β by CD4 + and CD8 + T cells. BM‐MSCs displayed a striking inhibitory action over T cells from RA patients, reducing the expression of cytokines involved in RA physiopathology. Remarkably, BM‐MSC‐derived immunomodulation affected either naive, effector, and memory T cells.